The AhR ligand phthiocol and vitamin K analogs as Pseudomonas aeruginosa quorum sensing inhibitors - Jia, Tianyuan; Liu, Dongjing; Bi, Xianbiao; Li, Menglu; Cai, Zhao; Fu, Jiapeng; Liu, Zhi; Wu, Pengyao; Ke, Xue; Jia, Aiqun; Zhang, Guoliang; Li, Guobao; et al. (Frontiers in Microbiology, 2022)
The aryl hydrocarbon receptor (AhR) protein senses microbial secreted metabolites to trigger the host innate immune system. The Pseudomonas quinolone signal (PQS) and Mycobacterium tuberculosis (MTb) metabolite phthiocol (Pht) are both ligands of AhR with similar chemical structures. Since PQS is an essential quorum-sensing molecule that regulates a wide range of virulence factors in P. aeruginosa, we hypothesized that Pht and its analogs are potential P. aeruginosa quorum-sensing inhibitors (QSIs) with immune-modulating functions. In this study, we demonstrated that Pht was able to inhibit the P. aeruginosa pqs QS system and reduce both biofilm formation and the production of pyocyanin. Molecular docking analysis suggested that Pht competes with PQS at the binding site of its receptor, PqsR. Electrophoretic mobility shift assay confirmed the Pht-PqsR interaction and showed that Pht attenuated PqsR from binding to the pqsA promoter. Proteomic analysis showed that synthesis of the key pqs QS proteins decreased upon the addition of Pht to the bacterial cultures. Furthermore, Pht analogs Vitamin K1 (Phylloquinone), K2 (Menaquinones), and K3 (Menadione) were also showed to inhibit the P. aeruginosa pqs QS system, while were able to activate the AhR signaling pathways. Our study suggests that the AhR ligands Pht and its Vitamin K analogs are promising QSIs for the alternative treatment of P. aeruginosa infections.